Advertising organizations and publications: a resource guide - Jones, John Philip (SAGE, 2000)
This is a comprehensive guide to the 77 key organisations and publications in the field of advertising and marketing communications. Entries include a thorough description of each organisation's purpose, activity and contact information
https://katalog.adlr.link/Record/0-1066688540